2018
DOI: 10.1016/j.jcis.2018.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved viscoelastic properties of self-assembling iron oxide nanocube superlattices probed by quartz crystal microbalance with dissipation monitoring

Abstract: Self-assembly of nanoparticles into superlattices can be used to create hierarchically structured materials with tailored functions. We have used the surface sensitive quartz crystal microbalance with dissipation monitoring (QCM-D) technique in combination with video microscopy (VM) to obtain time-resolved information on the mass increase and rheological properties of evaporation-induced self-assembly of nanocubes. We have recorded the frequency and dissipation shifts during growth and densification of superla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This two-step mechanism was confirmed by quartz crystal microbalance measurements with dissipation monitoring. 49 These investigations revealed that the disordered clusters retain certain solvation resulting in a viscous response and that the solvent is released upon mesocrystal formation.…”
Section: ■ Mesocrystalsmentioning
confidence: 99%
“…This two-step mechanism was confirmed by quartz crystal microbalance measurements with dissipation monitoring. 49 These investigations revealed that the disordered clusters retain certain solvation resulting in a viscous response and that the solvent is released upon mesocrystal formation.…”
Section: ■ Mesocrystalsmentioning
confidence: 99%
“…Especially if the particles are micrometer sized, they can be directly observed in an optical light microscope. For instance, Gasser et al were able to analyze the nucleation of large particles using confocal microscopy, while Bergström et al investigated the growth of ordered arrays of iron oxide nanocubes. Light microscopy is indeed a convenient analytical method as it is easier in handling compared to liquid cell TEM, and its resolution is high enough to detect the initial stages of the growth of nanoparticle superstructures. Another advantage of using colloidal nanoparticles as model systems for investigating nucleation is the possibility of controlling the interparticle potentials, thereby enabling precise tuning of their interactions and control over the formation of superstructures. , In this way, the assembly of colloidal nanoparticles with different morphologies can be governed to produce an array of structures, from NaCl to clathrate-like crystals. , Such control over the nanoparticle behavior can be even further extended to rule their interaction with different surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocube sizes and polydispersities were estimated by fitting a cubic model to the form factor, giving values of 6.8 ± 0.3 nm for NC068 and 9.1 ± 0.5 nm for NC091 (Figure S2), which corresponds very well to the edge lengths measured with transmission electron microscopy. 10,11 The deviation from the cuboidal model at low scattering angles in the SAXS patterns measured in the levitating drops at times exceeding 1180 and 800 s for the NC068 and NC091 dispersions, respectively, indicates that clusters were formed in the shrinking levitating drops (Figure 1c, red curves). The absence of any structural peaks suggests that the NC clusters were disordered.…”
Section: Resultsmentioning
confidence: 99%
“…Assembly of nanoparticles into superlattices or mesocrystals is a promising pathway to produce nanostructured materials with tunable properties. Superlattices that display not only a long-range translational order but also atomic coherence, i.e. , mesocrystals, are materials with unique properties that are attractive for optoelectronic and biomedical applications. Assembly of polyhedral nanocrystals into structurally diverse mesocrystals is controlled by the composition, size, and shape of the nanoparticles and the conditions during assembly. Several methods are used to assemble nanoparticles, with the evaporation-driven increase of the particle concentration being the most widely used. …”
mentioning
confidence: 99%